ePrivacy legislation in Europe – possible future legal and economic consequences - Sargsjans, Andrejs (Riga Graduate School of Law, 2020)
ePrivacy is one of the most important spheres of IT law in online business industry and infrastructure of digital market operations. ePrivacy covers and Regulates protection of personal data of common and professional users. Issue of that field of law is the fact that IT technology rapidly changes and forces authorities to change law according to the newest technologies and principles. Now ePrivacy legislation in Europe stands in front of decision to replace existing Directive 2002/58/EC and replace it with ePrivacy Regulation, what would entail a multitude of consequences both in legal and business spheres. It is necessary to understand that ePrivacy is first thing which reflects on the whole IT industry, because it covers cookies, general terms agreements on the webpages and processing of personal data. This research gives an opportunity to clarify main arguments for implementation of ePrivacy Regulationtion proposal and against it and makes the reader capable to understand why discussion among EU authorities takes place for three years on this moment.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Information technology law; Online business; Data protection